Does working beyond the statutory retirement age have an impact on health and functional capacity? The Finnish Retirement and Aging cohort study - KC Prakash; Virtanen Marianna; Pentti Jaana; Kivimäki Mika; Vahtera Jussi; Stenholm Sari (BMJ Publishing Group, 2022)
Objective This study aimed to compare the development of self-rated health, psychological distress and physical functioning between those retired on time and those who continued working beyond the individual retirement age.
Methods The study population consisted of 2340 public sector employees from the Finnish Retirement and Aging study. Participants were categorised into no extension of employment (retired at the individual retirement date or <3 months past) and extension of employment (≥12 months). Propensity score matching (1:1 ratio) was used to identify comparable group of participants in the no-extension (n=574) and extension (n=574) groups by taking into account preretirement characteristics and their interactions.
Results The prevalence of suboptimal self-rated health and psychological distress changed a little among the extension group during the follow-up from 1 year before (T1) to 18 months (T2) and 30 months (T3) after individual pensionable date. Compared with no extension, the risk of having suboptimal self-rated health in the extension group was 0.89 (95% CI 0.68 to 1.17) at T1, 1.16 (95% CI 0.88 to 1.53) at T2 and 0.96 (95% CI 0.68 to 1.37) at T3. For psychological distress, the corresponding risk ratios were 0.93 (0.65 to 1.32), 1.15 (0.78 to 1.69) and 1.04 (0.61 to 1.79). The mean differences in the number of physical functioning difficulties between the extension and no-extension groups were 0.06 (−0.16 to 0.29) at T1, 0.05 (−0.18 to 0.27) at T2 and −0.11 (−0.39 to 0.17) at T3.
Conclusions This study found no evidence that voluntarily extending the working career beyond retirement age would pose a risk to health and physical functioning among ageing workers.